Some anatomopathologlc characterlstics of the acquired Immunodeficiency syndrome (AIDS). - Takano, Juan (1989)
We present two cases of AIOS with biopsy and autopsy studies, belonging to the Air Force Central Hospital of Peru. One of them is a 27 years old man, homosexual, who was living in the United States of North America until 1982, during eight years. The other one is a 35 years old woman, married, whose husband was proved to be infected by the HIV-1 one week later the patient died. Among the pathological changes founded in biopsy and autopsy material, there was lymphadenopathy type II in both male and female patients; and later lymphadenopathy type III in the male patient. We also found lymphoid tissue atrophy of the spleen and of intestinal tract. Another lesion due to HIV-1 seen in the male case are foci of demyelination, inflammatory infiltrates and microglial nodules in the brain and cerebellum. In the male case was there generalized infection due to Cryptococcus neoformans and in the female case we detected Citomegalovirus in several tissues with acute pneumopathy. There was history of psoriasis in both cases, with active lesions at the time of death in the male case. Kaposi's sarcoma of the skin was detected in the female case. We discuss the pathological changes observed in both of our cases of AIDS (An Fac Med UNMSM II Epoca 1989; 1 (1-2): 19-26)